(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Indian society is still regarded as conservative and well cultured society owing to its shared family structure since ancient times. Family plays very significant role in growth of infants. The effect of globalization and modernization culminated into splitting of conventional structure of joint family into nuclear family in India. The Joint and nuclear all forms of structures of families have their own benefits and drawbacks in terms of raising of children and supplying services to family members.Family is the most significant primary community in culture and immediate social setting to which an infant is developed and exposed. A child learns to adapt in different fields of life according to the ideals principles given by his or her relatives. So, a family form influences a child ’s transition level at a wide degree and differently in girls and boys. The key objective of current research paper to evaluate social change Psychological impact upon students belong to nuclear and joint family structure of Pakistan. The study was composed of 160 students (80 male and 80 female) belonging to various family structures. The research was delimited to the students of schools.